A REVIEW OF THE CONTEMPORARY MOSQUE ARCHITECTURE - Özçakı, Meltem (Border Crossing, 2018)
Religious buildings, since the very early ages, are structured through time in accordance with the social structures, changing belief systems, cultural differences, and technological developments. Each civilization studied the period prior to them, benefited from the past knowledge, and developed their own authentic architecture. An evaluation of the contemporary Turkish mosques shows that, instead of building through an understanding of past buildings, replicating structures have been built. Considering the number and characteristics of these practices, it is important that only a few mosques constitute architectural examples. The article examines the reasons why small number of modern mosques has been built whilst the new built mosques replicate the old architectural designs. The issue is discussed with reference to the idea of an “unchanging mosque typology; idealizing a particular era and style; ignoring the developments in technology and material resources; continuing with the accustomed style”. Throughout the concepts such as Islamic Architecture, Ottoman Architecture, social structure, aesthetic perception, meaning, material resources, approaches in ideological and design realms, the longing for past and criticism of the global are used. In the article, a project for Halide Edip Adıvar Complex National Architectural Project Competition is highlighted as a case which is designed by team members: Meltem Özçakı (leader), Yağız Ezer, Ali Derya Mutlu, Büşra Şık, Ecem Kocaarslan, Canan Ganiç and assistants: Mahmut Nimetoğlu, Kübra Çelik. The article ends with a commentary on traditional structures in the context of contemporary opportunities available through new technologies and materials.